Development of quality indicators for the care of patients with chronic kidney disease : Results of a structured consensus process using the Delphi technique - Sierocinski, Elizabeth; Dröge, Lina; Chenot, Jean-François; Ebert, Natalie; Schäffner, Elke; Bothe, Tim; Mielke, Nina; Stracke, Sylvia; Kiel, Simone (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2023)
Chronic kidney disease (CKD) is a common condition, especially in the elderly. In order to prevent progression and complications of the disease, guideline-adherent outpatient care of patients with CKD should be prioritized. Quality indicators (QIs) can be used to measure and evaluate the quality of ambulatory care for patients with CKD. QIs specifically made for evaluating CKD care in Germany are not yet available. The goal of this work was to develop QIs for the quality assessment of outpatient care for patients over the age of 70 with CKD not requiring dialysis. QIs were operationalized from the recommendations of the German national guideline for CKD and others were proposed based on a published review of international QIs. The resulting QIs were divided into sets based on routine data (e.g., health insurance billing data) and data collection in practices (chart review). A panel of experts from various disciplines as well as a patient representative evaluated the proposed QIs in a two-stage Delphi process via online survey in October 2021 and January 2022 and a final consensus conference in March 2022. In addition, ranking lists of the most important QIs from each set were created. An incidence indicator and a prevalence indicator were established; these were not subject to vote. Further, 21 QIs were voted upon by the expert panel. The seven most important QIs in each set (billing data or chart review) were selected. Only one QI was rated by the expert panel as not suitable for additional use in adults under the age of 70 years. The QIs will enable the evaluation of the quality of outpatient care for patients with CKD with the long-term aim of optimizing guideline-adherent outpatient care.